Utilization of commercial collagens for preparing well-differentiated human beta cells for confocal microscopy - Brennecke, Brianna R.; Yang, USeong; Liu, Siming; Ilerisoy, Fatma S.; Ilerisoy, Beyza N.; Joglekar, Aditya; Kim, Lucy B.; Peachee, Spencer J.; Richtsmeier, Syreine L.; Stephens, Samuel B.; Sander, Edward A.; Strack, Stefan; et al. (Frontiers in Endocrinology, 2023)
With technical advances, confocal and super-resolution microscopy have become powerful tools to dissect cellular pathophysiology. Cell attachment to glass surfaces compatible with advanced imaging is critical prerequisite but remains a considerable challenge for human beta cells. Recently, Phelps et al. reported that human beta cells plated on type IV collagen (Col IV) and cultured in neuronal medium preserve beta cell characteristics. Here, we examined human islet cells plated on two commercial sources of Col IV (C6745 and C5533) and type V collagen (Col V) for differences in cell morphology by confocal microscopy and secretory function by glucose-stimulated insulin secretion (GSIS). Collagens were authenticated by mass spectrometry and fluorescent collagen-binding adhesion protein CNA35. All three preparations allowed attachment of beta cells with high nuclear localization of NKX6.1, indicating a well-differentiated status. All collagen preparations supported robust GSIS. However, the morphology of islet cells differed between the 3 preparations. C5533 showed preferable features as an imaging platform with the greatest cell spread and limited stacking of cells followed by Col V and C6745. A significant difference in attachment behavior of C6745 was attributed to the low collagen contents of this preparation indicating importance of authentication of coating material. Human islet cells plated on C5533 showed dynamic changes in mitochondria and lipid droplets (LDs) in response to an uncoupling agent 2-[2-[4-(trifluoromethoxy)phenyl]hydrazinylidene]-propanedinitrile (FCCP) or high glucose + oleic acid. In conclusion, an authenticated preparation of Col IV provides a simple platform to apply advanced imaging for studies of human islet cell function and morphology.